Effective typification of Avena pubescens (Poaceae; Pooideae) - Ferrer Gallego, Pedro Pablo (Mediterranean Botany, 2022)
Avena pubescens Hudson was previously considered to have been “neotypified” by Röser in 1995 from a specimen preserved at WU herbarium (Wien). However, there is an original element that was included and cited in the protologue. Therefore, the typification by Röser is here briefly discussed and superseded because is being contrary to Art. 9.8 of the International code of nomenclature for algae, fungi, and plants (Shenzhen Code). The name is lectotypified in this paper with an illustration published by Ray in 1724. In addition, for a precise circumscription of the name, an epitype is proposed from a complete and well preserved specimen at WU.